Ultrasonic Functionalized Egg Shell Powder for the Adsorption of Cationic Dye: Equilibrium and Kinetic Studies - Veluru Sridevi; B. Senthil Rathi; P. Senthil Kumar; A. Saravanan; R. V. Hemavathy; S. Karishma; S. Jeevanantham; Sri Himaja Pamu; Lam Sudha Rani; K. S. N. V. Prasad (Adsorption Science & Technology, 2022)
The present research focuses on synthesizing surface-modified egg shell powders using ultrasonic modification method for the effective adsorption of malachite green dye (MG). The presence of functional groups and surface morphology of ultrasonic-assisted egg shell powder (UAESP) was characterized using Fourier transform infrared spectrophotometer (FTIR) and scanning electron microscopy (SEM) analysis, respectively. A batch adsorption study was performed to predict the optimum conditions, and the results showed that maximum adsorption rate at the solution pH of 8.0 within the interaction time of 90 min, dosage of 1.5 g/L for MG dye concentration of 25 mg/L, and temperature 30°C. The isotherm and kinetics modeling of the present adsorption system can be well described by Freundlich and pseudosecond-order kinetics, respectively. The monolayer adsorption capacity of UAESP for MG dye was originated to be 64.58 mg/g. The results of the thermodynamic study reported that adsorption removal of MG dye onto UAESP was exothermic and spontaneous. This study accredited that UAESP has higher efficiency, cost-effective, and sustainable adsorbent for the removal of hazardous dyes on an industrial level.